Determination of explosion parameters of LPG-air mixtures in the closed vessel - Mohd Saifol, Ishak (2008)
The experimental results of the measurements of the explosion pressure and rate of explosion pressure rise as a function of propane/butane concentration in the mixture with air in the 20 L explosion chamber are tested. The research was aimed at determination of the explosion pressure and limits. The influence of initial temperature of the mixture (changing in the range of 293–473 K) on the fundamental explosion parameters was also investigated. The ignition source was an induction electrical spark. It was stated, that the increase of initial temperature of the LPG-air mixture causes a significant increase of the explosion range. From the experimental result, the concentration of LPG and air mixture just explodes at the range 2% to 10% of LPG in air. The concentration of LPG at 4% gives the highest value of explosion pressure which at this condition, an explosion of LPG becomes very dangerous. The highest of deflagration index for LPG is 29. So, the designing of LPG tank storage should have value of deflagration index more than 29 to resist the over pressure from happen. The change of concentration of the LPG-air mixture causes a significant effect to maximum explosion pressure and maximum rate pressure rise. But it not means that the more concentration of LPG in air will increase the explosion pressure.